Coverage of Adolescent Substance Use Prevention in State Frameworks for Health Education: 10‐Year Follow‐Up. (18th December 2012) - Seitz, Christopher M.; Wyrick, David L.; Orsini, Muhsin M.; Milroy, Jeffrey J.; Fearnow‐Kenney, Melodie
Abstract : BACKGROUND: The use of alcohol, tobacco, and other drugs (ATOD) by adolescents is a national health issue. One way in which the United States approaches the prevention of substance use among adolescents is by teaching high school students about ATOD at school. The curriculum for health education courses is based upon each state's framework. The purpose of this study was to conduct a 10‐year follow‐up to a study that analyzed state frameworks for key mediators of adolescent substance use. METHODS: Researchers performed an extensive content analysis of all 50 states' curriculum frameworks for high school health education to identify if, and to what degree, key mediators of adolescent substance use were included in each state's curriculum framework. After training, inter‐rater agreement was greater than 95%. RESULTS: Mediators identified most often in the 50‐state curriculum frameworks for high school health education were beliefs about consequences, decision making, social skills, assistance skills, and goal setting. Twenty‐two of 50‐state curriculum frameworks for high school health education had dedicated sections for ATOD. CONCLUSION: There were modest improvements since 2001 in the inclusion of mediators of adolescent substance use within state curriculum frameworks. There still exists many opportunities to more effectively use curriculum frameworks to improve classroom health instruction.